REVITALISASI PENDIDIKAN VOKASI DI INDONESIA: TRANSISI SEKOLAH KE DUNIA KERJA MELALUI FILOSOFI PENDIDIKAN MOH. SJAFEI [REVITALIZING VOCATIONAL EDUCATION IN INDONESIA: THE SCHOOL-TO-WORK TRANSITION THROUGH MOH. SJAFEI’S EDUCATIONAL PHILOSOPHY] - Tri Gunawan; Poerwanti Hadi Pratiwi (Universitas Pelita Harapan, 2026)
Indonesia's vocational education system faces ongoing challenges in facilitating the school-to-work transition. Despite various reform efforts, the high unemployment rate among vocational high school (SMK) graduates indicates a mismatch between educational outcomes and labor market needs. This study uses a Systematic Literature Review (SLR) of 60 primary source articles from Google Scholar to identify key themes affecting vocational education performance: school-to-work transition gaps, policy and implementation issues, curriculum and pedagogical transformation, institutional barriers, and limited integration of local wisdom and character education. These findings are analyzed through the philosophical lens of Moh. Sjafei, a pioneering Indonesian educator who emphasizes holistic, community-based, and practice-oriented learning. The results demonstrate that Sjafei's